Find what you can divide both 6ax and 9a by.
They can both be divided by 3, leaving 2ax and 3a.
These can both be divided by a, leaving 2x and 3.
So 6ax + 9a = 3a (2x + 3)
The factors of 6ax + 9a are 3a and (2x + a)
It is 3a(a+3) when factored
6ax2 + 6ax + 6a = 6a(x2 + x + 1)
34
12a + 6b + 9a + 14b =(12a + 9a) + (6b + 14b) =21a + 20b
(9a + 2)(9a + 2)
2a+5a+9a = 16a
a2+9a+20 = (a+4)(a+5) when factored
9a + 7b *remember to look and understand the letters!*
6ax2 + 15ax = 3ax(2x + 5)
9a+21 3(3a+7)
The simplified expression is -9a -9b.
There is nothing you can do to 9a + 5 without knowing the value of a.